Corporate image of Islamic banks in Malaysia: an institutional theory approach - Osman, Ismah; Abdullah, Kalthom; Abdullah, Nurdianawati Irwani; Haque, A. K. M. Ahasanul (2010)
The development of the Islamic banks in Malaysia is increasingly challenging with more conventional banks having their own Islamic bank subsidiaries participating and offering banking products and services based on Islamic principles after two decades of its establishment. Undoubtedly, it is very important for the players in the Islamic banking industry to better position themselves, in order to confront and respond vigorously to the robustness of the global financial environment. Hence, this study would embark on corporate image as this would be one of the most important criteria in determining customers’ patronage towards Islamic banking. More importantly, this study adopts the institutional theory approach since those banks offering Islamic banking products and services are considered homogenous. Exploratory study through interviews was conducted with customers, Syari’ah supervisors, practitioners and lecturers in Islamic banking as to gain insights pertaining to corporate image in Malaysia. Next, survey was conducted through self-administered face-to-face method, from Islamic banking customers in the Klang Valley. Exploratory factor analysis and confirmatory factor analysis were then employed for the data analysis. Consequently, it is hoped that this study would facilitate in developing the Islamic banks’ marketing strategies which are very crucial specifically due to the intense competition from the players of the industry.